If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10n + -1 = 71 Reorder the terms: -1 + -10n = 71 Solving -1 + -10n = 71 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -10n = 71 + 1 Combine like terms: -1 + 1 = 0 0 + -10n = 71 + 1 -10n = 71 + 1 Combine like terms: 71 + 1 = 72 -10n = 72 Divide each side by '-10'. n = -7.2 Simplifying n = -7.2
| 175=-16t^2+100t | | 35+(-13)+(+8)-(-6)= | | (38-((x*7)+x))+((x*7)+x)=38 | | 54.5+10.5x= | | 764=4(x+19) | | 7a-3b+8a-5b= | | 10.5+54.5x= | | (x*x)+2x=120 | | 2x^2+9x-45=0 | | -12=2x+4 | | -8x+(-16)=24 | | 5p+7-5p=-7*(p-3) | | 5p+7-5p=7*(p-3) | | 3(3-1)=x | | 96.3=9(m+2.4) | | (4b+5)+(4b-2)= | | -2(3y-4)+6= | | 3(3-1)= | | y-2=-13 | | 7x-36=b | | 1/7x-y=18 | | 8.4(x-3.25)=-25.2 | | 5mn+3nm= | | 114=-16t^2+95t+0 | | 4x+(-4x)+4+2x= | | 60=x+.07x | | x^3+7x^2-64x-448=0 | | 3x^2+(1+2i)x+1-i=0 | | -5/2x=-10 | | 98=7x+35 | | (x^2+9x-5)(x^2+8x-3)=0 | | 7x-36= |